Potential for the establishment of Cylas punticollis Boheman (Coleoptera: Apionidae) as a pest of sweetpotato in Lesotho - Schoeman, A.S. (University of Pretoria, 2013)
Dissertation (MSc (Entomology))--University of Pretoria, 2007.